Pengembangan Media Video Animasi Materi Pengukuran Pada Pembelajaran Matematika Untuk Kelas II Sekolah Dasar - Ningsih, Sri Yunimar; Anggrayni, M; Sita, Elma (Jurnal Ilmiah Dikdaya, 2024)
This research was motivated by students' lack of understanding in participating in learning activities, especially in learning mathematics. This research aims to produce animated video media for measurement material in mathematics learning for class II elementary schools that is valid and practical. The type of research used is R&D (Research and Development), or development research, using the ADDIE model, (Analyze, Design, Development, Implementation, Evaluation). It has 5 stages including: first analysis (analysis of needs, characteristics of students and materials), second design (preparation of animated videos). Third development (animation video validation test). Fourth, implementation (practicality test), and finally evaluation (feasibility test of animated video products). This development research obtained results from validation tests by four expert validators with an average score of 81.25% in the very valid category, the practicality test was carried out by the class II teacher with an average score of 100% in the very practical category. The test results seen from the student response questionnaire obtained an average score of 91.56% in the very practical category. Based on the results obtained, it can be concluded that the animated video media measuring material in mathematics learning for class II elementary schools is very valid and practical. Based on the results of the validity and practicality related to products made regarding animated video media, it can be said that the media created is very suitable and suitable for use in elementary schools. Therefore, the product created is said to be valid, practical and effective for use in the learning process in elementary schools.